DISCOVERY LEARNING IN TEACHING REPORT WRITING FOR JUNIOR HIGH SCHOOL STUDENTS BASED ON 2013 CURRICULUM - Mushtoza, Dina Amaliyah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2016)
This study focuses on how the implementation of DL in teaching report writing for junior high school students based on 2013 curriculum. It has three research questions: (1)how is the implementation of DL in teaching report writing, (2) how are the students’ responses towards DL during the teaching learning of report writing, (3) how is the students’ writing report after taught by implementation of DL.This study used qualitative research. It focuses on natural setting, has an interest in meaning, the perspective emphasizes on a process, concern with an inductive analysis and grounded theory. The data collection techniques are observation and interview to anstablewer the first and second research questions, and documentation to answer first and third research questions.The result of this study reveals when teaching report writing, the teacher implements DL which is relevant and appropriate with the theories. He uses six steps, (1) stimulation (2) problem statement (3) data collection (4) data processing (5) verification (6) generalization. The students’ responses are positive in five steps, except data processing, the students’ response is negative, because of limited time. In all of the writing, the teacher gives his comments. It makes students pay attention to their result, and know their mistakes as motivational correction for them. All of students’ score isstill high of the standard score.